Do Pilot and Demonstration Projects Work? - Christopher J. Blackburn; Mallory E. Flowers; Daniel C. Matisoff; Juan Moreno-Cruz (Center for Economic Studies and ifo Institute (CESifo), 2018)
Pilot and demonstration (P&D) projects are commonly deployed to catalyze early adoption of technology, but are poorly understood in terms of mechanism and impact. We conceptually distinguish unique functions of pilots and demonstrations, then examine whether they accelerate green building adoption. To identify effects of P&Ds on adoption, we develop a difference-in-difference-in-differences strategy, exploiting variation in location, technologies, and timing of P&D projects. Results indicate a 12% increase in adoption rates within markets affected by P&D projects. Further analyses examine mechanisms driving this effect. Subsequent results suggest green building demonstration projects create learning externalities, proliferating technology diffusion under certain conditions.
Keywords: O33; Q55; D83; 330; information spillovers; peer effects; social learning; pilot and demonstration projects; technology adoption; diffusion; policy evaluation; green building